2020
DOI: 10.3390/nu12020408
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of a Low-dose of Conjugated Linoleic Acid on Body Weight Gain and other Cardiometabolic Risk Factors in Cafeteria Diet-fed Rats

Abstract: Conjugated linoleic acid (CLA) is a dietary supplement that has been shown to improve obesity. However, some authors have associated high doses of CLA supplementation with liver impairment and insulin resistance. The aim of this study was to assess whether the consumption of low doses of CLA maintained the beneficial effects on the main metabolic disturbances associated with metabolic syndrome (MetS) but prevented the occurrence of non-desirable outcomes associated with its consumption. Male Wistar rats, fed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
1
3
1
Order By: Relevance
“…In addition, we showed the ability of DHA/EPA in decreasing anxiety-like behaviour in obese rats. Otherwise, despite the evidence showing the role of omega-3 in the improvement of metabolic profile (37,38) , we found that DHA/EPA was not able to revert weight gain, adiposity, lipidic profile, and hepatic levels of TNF-α in CAF-fed rats. Thus, by using CAF, a highly obesogenic diet, we are showing for the first time that DHA/EPA beneficial effects might depend on the severity of the obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we showed the ability of DHA/EPA in decreasing anxiety-like behaviour in obese rats. Otherwise, despite the evidence showing the role of omega-3 in the improvement of metabolic profile (37,38) , we found that DHA/EPA was not able to revert weight gain, adiposity, lipidic profile, and hepatic levels of TNF-α in CAF-fed rats. Thus, by using CAF, a highly obesogenic diet, we are showing for the first time that DHA/EPA beneficial effects might depend on the severity of the obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…In this sense, regardless of the photoperiod, the CAF notably altered the liver weight, as well as all the hepatic biochemical parameters mea-sured, including the total lipid content, TC, TAG, and phospholipids. These results are in accordance with other studies that exhibited an increase in hepatic lipid-related parameters promoted by the CAF [55][56][57]. Therefore, the maintenance of lipid accumulation in the liver promoted by the CAF could, ultimately, lead to NAFLD, since hepatic lipid accumulation is a comorbidity of this pathology [58].…”
Section: Discussionsupporting
confidence: 92%
“…According to studies by other authors, long-chain unsaturated fatty acids are important in the human diet 52 , 54 , 55 . Replacing SFA with PUFA in the human diet is beneficial for the cardiovascular system 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ANXA9/Nla III polymorphism analysis for AA homozygous animals, a decrease in the C20:4n6 acid level was found, which can also be considered a favourable phenomenon. Supplementation of CLA in the diet of animals and humans improves the metabolism of glucose and lipids in the body 55 . In our research, an increase in the level of CLA in the milk of sheep with the GG ANXA9/Hin fI genotype was observed.…”
Section: Discussionmentioning
confidence: 99%